Work environment risks for health care workers with cystic fibrosis. Issue 12 (14th September 2018) - Bell, Scott C.; Armstrong, David; Harrington, Glenys; Jardine, Luke; Divakaran, Rebekah; Loff, Bebe; Middleton, Peter G.; McDonald, Tim; Rowland, Karen; Wishart, Michael; Wood, Michelle E.; Stuart, Rhonda L.
ABSTRACT: In Australia and New Zealand, >50% of people with cystic fibrosis (CF) are adults and many of these people are pursuing vocational training and undertaking paid employment. More than 6% of adults with CF are working in health care. There is limited guidance in literature to support health care workers with CF (HCWcf) in training and in employment to support safe practice and to provide protection for themselves and their patients from the acquisition of health care associated infection. A multidisciplinary team of CF and Infectious Disease Clinicians, Infection Prevention and Control Practitioners, HCWcf, academic experts in medical ethics and representatives from universities, appraised the available evidence on the risk posed to and by HCWcf. Specific recommendations were made for HCWcf, CF health care teams, hospitals and universities to support the safe practice and appropriate support for HCWcf.